2020
DOI: 10.1002/jcsm.12530
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin stimulates mitochondrial biogenesis in insulin resistant muscle via activation of AMPK pathway

Abstract: Background Skeletal muscle is mainly responsible for insulin‐stimulated glucose disposal. Dysfunction in skeletal muscle metabolism especially during obesity contributes to the insulin resistance. Astaxanthin (AX), a natural antioxidant, has been shown to ameliorate hepatic insulin resistance in obese mice. However, its effects in skeletal muscle are poorly understood. The current study aimed to investigate the molecular target of AX in ameliorating skeletal muscle insulin resistance. Methods We fed 6‐week‐old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 78 publications
(165 reference statements)
6
130
1
Order By: Relevance
“…In this study, ASX administration significantly ameliorated insulin resistance and glucose intolerance through the regulation of 5 adenosine monophosphate-activated protein kinase (AMPK) activation in the muscle, independent of its antioxidant activity. In addition, it stimulated muscle mitochondrial biogenesis [73].…”
Section: Antidiabetic Effects Of Astaxanthinmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, ASX administration significantly ameliorated insulin resistance and glucose intolerance through the regulation of 5 adenosine monophosphate-activated protein kinase (AMPK) activation in the muscle, independent of its antioxidant activity. In addition, it stimulated muscle mitochondrial biogenesis [73].…”
Section: Antidiabetic Effects Of Astaxanthinmentioning
confidence: 99%
“…Moreover, ASX potentiates post-receptor insulin signaling events by enhancing the autophosphorylation of insulin receptor-β (IR-β), IRS-1 associated PI3-kinase step, phospho-Akt/Akt ratio, and GLUT-4 translocation in skeletal muscles [72]. Yasuhiro Nishida et al also showed improved glucose metabolism by enhancing glucose incorporation into skeletal muscles in ASX-treated HFD mice [73]. In this study, ASX administration significantly ameliorated insulin resistance and glucose intolerance through the regulation of 5 adenosine monophosphate-activated protein kinase (AMPK) activation in the muscle, independent of its antioxidant activity.…”
Section: Antidiabetic Effects Of Astaxanthinmentioning
confidence: 99%
“…This is consistent with a previous study showing that Ast treatment significantly enhanced insulin-stimulated phosphorylation of the Akt protein in high fat diet-fed mice. 12 Accordingly, Ast functions in promoting both transcription of IRS3and phosphorylation of the downstream protein Akt, which together contributed to the improved insulin sensitivity in the Ast-treated groups. We also observed that the CD36 gene, which functions in mitochondrial β-oxidation and free fatty-acid transport in the AMPK-signaling pathway, was expressed at much higher levels in the Ast-treated DM rats than the DM control rats ( Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…11 Oxidative stress in streptozotocin (STZ)-induced DM rats is inhibited by combination treatment of Ast with α-tocopherol. 12 Figure 1 (A) Chemical structure of Ast; (B) pipeline for identification of both predicted and detected Ast targets that integrate compound proteins, disease proteins, RNAseq analysis, GO analysis, docking, and network construction. Recently, Ast treatment has been reported to be involved in stimulating mitochondrial biogenesis and significantly ameliorating insulin resistance through activation of the AMPK pathway in skeletal muscle.…”
Section: Astaxanthinmentioning
confidence: 99%
“…A similar effect of AST was shown for cancer [ 49 ]. Partial prevention of elimination of the components of the damaged respiratory chain complexes in ISO-injected rats ( Figure 2 ) may be related to the stimulation of mitochondrial biogenesis by AST [ 50 ].…”
Section: Discussionmentioning
confidence: 99%